Religious Courts in Indonesia and Malaysia: History, Structure, and Jurisdiction - Azzahra, Raihan; Shuaib, Farid Sufian (Universitas Muhammadiyah Yogyakarta, 2022)
As Muslim-majority countries, Religious Court plays an important role in resolving disputes among Muslims both in Indonesia and Malaysia. This doctrinal legal study employs comparative approach. Comparison is made between the Indonesian Religious Court and the Malaysian Religious Court, particularly in terms of history, structure, and jurisdiction. The result of this study shows that there are some commonalities and differences. Regarding the commonalities, Religious Courts from both countries have a long evolution in three various periods of history, both countries' Religious Courts are mostly organized into three levels, and they both share the same jurisdiction of the courts that only Muslims are subjected to their jurisdictions. For the differences, the history of Religious Courts in Indonesia and Malaysia were influenced by different colonials, all Religious Courts in Indonesia have an integrated and hierarchical structure, while in Malaysia, the structure is separated from one state to another, and the jurisdiction indicates that Indonesia has law uniformity, whereas Malaysia is not uniform in all states